2012
DOI: 10.1074/jbc.m112.392142
|View full text |Cite
|
Sign up to set email alerts
|

Obatoclax, Saliphenylhalamide, and Gemcitabine Inhibit Influenza A Virus Infection

Abstract: Background: Novel options should be developed for treatment of IAV infections. Results: Obatoclax, saliphenylhalamide, and gemcitabine target host factors and inhibit IAV and several other viruses infections. Conclusion: These compounds represent potent antiviral agents. Significance: These compounds could be exploited in treatment of severe viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
128
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 28 publications
9
128
0
Order By: Relevance
“…Strikingly, the accumulation of MK2206 in the vesicles was abrogated by inhibitors of cellular v-ATPase and Mcl-1 (Fig. 1D) (6,8,20). These results suggest that endosome acidification and Mcl-1 function are required for MK2206 accumulation in the vesicles in cytoplasm.…”
Section: Agentsupporting
confidence: 48%
See 1 more Smart Citation
“…Strikingly, the accumulation of MK2206 in the vesicles was abrogated by inhibitors of cellular v-ATPase and Mcl-1 (Fig. 1D) (6,8,20). These results suggest that endosome acidification and Mcl-1 function are required for MK2206 accumulation in the vesicles in cytoplasm.…”
Section: Agentsupporting
confidence: 48%
“…It was proposed that temporal inhibition of proviral cellular functions with small molecules is less likely to elicit viral drug resistance (6)(7)(8). There are dozens of commercially available small molecules that inhibit cellular functions.…”
mentioning
confidence: 99%
“…We infected MDCK cells with WSN-202, WSN-220 or WSN-230 viruses at an m.o.i. of 0.01 following the procedure described by Denisova et al (2012). We found that WSN-202, WSN-220 and WSN-230 viruses replicated efficiently in MDCK cells (Fig.…”
mentioning
confidence: 85%
“…Human monocyte-derived macrophages serve as an excellent cellular model for studying antiviral responses, because alveolar macrophages represent primary targets for influenza virus infection (Denisova et al, 2012 To monitor the effect of NS1 C-terminal truncations on antiviral responses, we infected macrophages with WSN-202, WSN-220 or WSN-230 virus at an m.o.i. of 2.…”
mentioning
confidence: 99%
“…The most significant canonical pathways specifically associated with virus infections, according to gene set enrichment analysis (GSEA; www.broadinstitute.org/gsea, [16]), were interferon-α, -β, and -γ signaling, cytokine signaling, [10][11][12][13]. These molecules should be first evaluated in vitro using antiviral efficacy assays, and then in animal models as described in our previous studies [14]. The immuno-modulatory effects of these drugs should also be studied, followed by drug resistant tests as in ref.…”
Section: Combination Of Various Omics Techniques Identifies Potentialmentioning
confidence: 99%